Chronicles of HBV and the Road to HBV Cure - Rukaiya Bashir Hamidu; Richard R. Hann; Hie-Won Hann (Livers, 2023)
Chronic hepatitis B remains a major public health concern and a leading cause of morbidity and mortality worldwide, specifically through its causative role in chronic liver disease and hepatocellular carcinoma. Worldwide, it affects up to 292 million people. In this paper, we review the historic discovery of the hepatitis B virus and chronicle the significant advances in our understanding of the virus and its interactions with the human host to cause disease. We also overview advancements in therapies for hepatitis B virus and the current absence of curative therapies and highlight on-going therapeutic efforts in search of curative therapies to control transmission and eradicate hepatitis B virus.